Feasibility study of palm oil clinker as environmentally friendly self-compacting concrete / Jegathish Kanadasan - Jegathish , Kanadasan (2016)
The environmental problems resulting from a myriad of improper waste management issues have been on the rise for the past few decades. Some of these wastes have a high potential to be converted into usable materials to avoid excessive use of natural resources. In this study, the incorporation of palm oil clinker (POC), a waste from the palm oil mill as a lightweight aggregate for the production of self-compacting concrete (SCC) was researched thoroughly. A complete characterisation study on POC was carried out to understand its physical, chemical and microstructural properties. POC specimens were collected from the respective states throughout Malaysia to identify the variations and the likely causes leading to differences. Since POC is lightweight, porous and irregular in shape, a new mix design methodology was required to accommodate these properties to boost the fresh and hardened SCC properties. Particle packing (PP) concept was developed to suit the special POC characteristics. The void volume and the packing values were analysed and later integrated into a mix proportion. POC powder was introduced instead of using excessive amount of cement to supplement the need for extra paste. Fresh properties of SCC were determined and checked against a normal accepted standard to ensure they comply with the regulated limits. The hardened properties of the concrete were determined through compressive strength, flexural strength, splitting tensile strength and modulus of elasticity. The long-term behaviour of the concrete was investigated through a series of durability tests. As this study focuses on the use of waste material, a sustainability assessment is necessary to highlight the advantages and contributions. This was carried out through a complete greenhouse gas emission study, life cycle assessment, cost efficiency and energy efficiency. Smaller variations in strength and sustainability properties of the POC specimens throughout Malaysia indicate the adaptability of the material to be used in concrete. POC powder, a new material introduced in this study showed significant achievement in strength,engineering economic index (ECI) and engineering environmental index (EEI) by 71%, 26% and 42% respectively when 50% of cement is replaced. For mass production, POC powder can save about 3.3% of cement for every tonne of crude palm oil produced. Generally, substitution of POC has the ability to produce almost 70% to 78% strength properties of the conventional concrete, making it feasible to be used in construction industry. Sustainable assessment carried out showed that the EEI and ECI for POC concrete were enhanced by 25% and 36% respectively. From durability standpoint, POC showed significant improvement at a longer assessment period indicating the quality of the waste material. Parallel with the principle of ‘research leading towards applications’, two products namely palm oil clinker ornament (POCON) and palm oil clinker drain (POCDRA) were designed and tested for commercial use. POC which is being disposed off without any value definitely would provide a much needed impetus to the construction industry by supplementing quality aggregates and cement alternative. In a nutshell, this research has enabled the successful utilization of POC for the production of SCC